2011
DOI: 10.4319/lo.2011.56.6.1976
|View full text |Cite
|
Sign up to set email alerts
|

Unprecedented slow growth and mortality of the rare colonial cyanobacterium, Nostoc zetterstedtii, in oligotrophic lakes

Abstract: Centimeter-large colonies of Nostoc zetterstedtii from a Swedish oligotrophic lake had the lowest growth and mortality rates of any studied temperate macrophyte. Annual growth rates at two shallow sites averaged 0.57-0.73 3 10 23 d 21 , corresponding to doubling times of colony dry weight in 2.6-3.3 yr. With such low growth rates, the largest colonies measuring 7 cm in diameter are 24-31 yr old. We found no mortality of incubated colonies and calculated the mortality rate to , 7.3 3 10 25 d 21 and the life spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 27 publications
2
12
0
Order By: Relevance
“…Oxygen values were converted to carbon values assuming a 1 : 1 molar ratio between exchange of O 2 and DIC as previously found for N. pruniforme and N. zetterstedtii (Raun et al ., ; Sand‐Jensen et al ., ). Colony dry weight was converted to organic carbon content (Col C ) using the measured average percentage of C to DW of 40.8% (Sand‐Jensen & Møller, ). Thus:RGRO2=lnfalse((ColnormalC+NPR)false(ColCfalse)1false)…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Oxygen values were converted to carbon values assuming a 1 : 1 molar ratio between exchange of O 2 and DIC as previously found for N. pruniforme and N. zetterstedtii (Raun et al ., ; Sand‐Jensen et al ., ). Colony dry weight was converted to organic carbon content (Col C ) using the measured average percentage of C to DW of 40.8% (Sand‐Jensen & Møller, ). Thus:RGRO2=lnfalse((ColnormalC+NPR)false(ColCfalse)1false)…”
Section: Methodsmentioning
confidence: 99%
“…Because N. zetterstedtii has a much harder and denser colony matrix than N. commune and N. pruniforme , it is expected to grow much more slowly than the other two species because of greater costs to produce and maintain the massive colony matrix. Investment in a dense and chemically well‐protected colony matrix should, on the other hand, ensure low mortality and extended survival, as previously shown for N. zetterstedtii (Sand‐Jensen et al ., ; Sand‐Jensen & Møller, ), illustrating the common trade‐off between growth and persistence (Sand‐Jensen & Borum, ; Cebrian & Duarte, ; Poorter et al ., ). We examined experimentally if observed growth rates and estimated growth rates from the photosynthetic–respiratory balance are indeed low for all three species and particularly low for N. zetterstedtii and whether growth rates decline as anticipated with increasing colony size of N. pruniforme and N. zetterstedtii .…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…In a previous study, the dominance of gelatinous taxa has indeed been shown to correlate with increased epilithon C:P and N:P ratios (Liess & Kahlert, ). In addition, Sand‐Jensen and Møller () observed molar ratios of C:P > 5,700 and of N:P > 680 in Nostoc zetterstedtii in a Swedish lake, but this appears to be an extreme value and more data are needed to describe the elemental stoichiometry of N 2 ‐fixing benthic cyanobacteria.…”
Section: Discussionmentioning
confidence: 99%